Boulez and Mallarmé: A Study in Poetic Influence - Breatnach, Mary (Aldershot Ashgate, 1996)
Mallarme died in 1898, but his centrality to the aesthetic thinking of the twentieth century is firmly established. Of this there exists no more striking affirmation than the association of his name with that of Boulez, a musician renowned for his commitment to the new. In the late 1950s, at a crucial point in his development, the composer chose the poet as his guide.In this study, Mary Breatnach looks at a fascinating irony in Boulez's choice. Mallarme's work is shown to be a special kind of 'music', set against the art of sounds with which we are familiar, in part a result of his avowed intention to take back from that art an allusiveness and structural complexity which, he believed, belonged to poetry.The central chapter focuses on Pli selon pli, Boulez's 'portrait of Mallarme'. Arguing that the originality and significance of the piece are inseparable from the poetry and, more particularly, from the literary thinking which inspired it, Dr. Breatnach shows that knowledge of that background serves as a heuristic aid to an understanding of the very nature of the music.The book concludes by defining the special place occupied by Pli selon pli in musical and aesthetic history.